Smallest Late Pleistocene inhabited island in Australasia reveals the impact of post-glacial sea-level rise on human behaviour from 17, 000 years ago. (1st October 2020) - Shaw, Ben; Coxe, Simon; Haro, Jemina; Privat, Karen; Haberle, Simon; Hopf, Felicitas; Hull, Emily; Hawkins, Stuart; Jacobsen, Geraldine
Abstract: Late Pleistocene records of island settlement can shed light on how modern humans ( Homo sapiens ) adapted their behaviour to live on ecologically marginal landscapes. When people reached Sahul (Pleistocene New Guinea-Australia), between 65 and 50 ka, the only islands they would have encountered were in the tropical north. This unique geographic situation therefore offers the only possibility of modelling human adaptive behaviour to islands in Australasia during the Late Pleistocene. Cave excavation on the uplifted limestone island of Panaeati in the Massim region of Southeastern New Guinea revealed a cultural sequence commencing from 17, 300–16, 800 cal. BP, suggesting habitation of higher coastlines occurred as low-lying shorelines destabilised during the initial stages of deglacial sea-level rise. No cave use was evident between 12, 400 and 4780 cal. BP when the continental shelf was fully inundated, and Panaeati reduced in size by 90%. It is likely that diminished coastlines and the reduced resources of low-lying islands could no longer support pre-agricultural populations during this time. Cultural groups that were better adapted to living on small islands returned to Panaeati by 4780–4490 cal. BP when sea levels had stabilised, lagoons formed, and coastal ecosystems had diversified. Investigations demonstrate the role of larger islands as refugia during deglacial sea-level rise and the effects on human dispersals and cultural diversity. Highlights: Settlement of the island by 17.3–16.8 ka during the onset of deglacial sea-level rise. Abandonment from 12.4 to 4.8 ka coincided with a 90% reduction in island size. Mid-Late Holocene habitation commenced after lagoons formed and sea levels stabilised. Cave sequence fits regional patterns of adaptive behaviours with changing climate. Large, high islands were refuges when low islands flooded.